AN INVESTIGATION ON STUDENTS’ PERCEPTION TO THE USE OF CODE-SWITCHING IN ENGLISH AS A FOREIGN LANGUAGE (EFL) CLASSROOMS - Manik, Cristina Geovani; Herman, Herman; Hutauruk, Bertaria Sohnata (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
This study investigates students’ perceptions of code-switching in English as a Foreign Language (EFL) classroom, focusing on how internal and external factors influence their attitudes and language use. Employing a descriptive qualitative research design, data were collected through questionnaires distributed to 60 Grade XI students from SMA YP HKBP 1 Pematangsiantar. The questionnaire measured perceptions related to internal factors such as confidence, motivation, and learning processes, as well as external factors including family background, peer influence, and classroom environment. The results indicate that most students view code-switching positively, reporting increased confidence and motivation when integrating Indonesian within English communication. Additionally, code-switching was found to reduce anxiety and enhance their ability to express ideas effectively. Social influences, especially peer behavior and classroom size, significantly affected their use of code-switching. Conversely, family influence was less impactful. These findings highlight that code-switching serves as both a communicative strategy and a supportive pedagogical tool in EFL learning. The study recommends that educators embrace code-switching to foster a more inclusive and effective language learning environment, particularly in multilingual contexts where students face challenges in expressing themselves solely in English. This research contributes to the understanding of bilingual communication dynamics in EFL settings and provides insights for language teaching practices that accommodate students’ linguistic and cultural realities.